Perancangan Sistem Informasi Presensi dan Nilai Siswa Berbasis Web pada Sds Muhamadiyah 35 Solear Menggunakan Metode Prototype - Ayu Silvia, Trisna; Roeslan Djutalov (Jurnal Riset Informatika dan Inovasi, 2023)
Currently, schools are expected to follow the development of science in the field of technology and information to support academic activities such as processing student report cards. SDS Muhamadiyah 35 Solear is one of the educational institutions that strives to follow various technological developments. To be able to support the process of teaching and learning activities, schools need a system that can assist in delivering information to several parties, one of which is the management of report cards which have been carried out manually. With a management system that is carried out in this way, it causes several problems and obstacles, including inaccurate management of student data such as there is the same student data and student data that is not appropriate.the way the previous report card worked only used a manual method, namely by entering each student's data into paper that had previously been made tamplate such as tamplate report card.this will cause data errors Students and the resulting data will be long so it takes a lot of time. For this reason, in this study, a Web-based Student Attendance and Value Information System Design was carried out at Sds Muhamadiyah 35 Solear Using the Prototype Method with the existence of this report card processing system can help homeroom teachers, school teachers in managing student report card data that is more practical and efficient, more structured and safer in storage. And can help homeroom teachers, teachers and parents in monitoring student learning activity. Keywords: Design of web-based attendance information system; student attendance application; waterfall method